PENGARUH NILAI TAKSIRAN DAN UJRAH TERHADAP KEPUTUSAN NASABAH DALAM MENGGUNAKAN PRODUK GADAI EMAS PADA PT BANK SYARIAH INDONESIA, TBK CABANG MEDAN KAMPUNG BARU - Iqbal Nur Hidayat; Aditya Amanda Pane; Rana Fathinah Ananda (Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the effect of estimated value and ujrah on customer decisions in using gold pawn products at PT Bank Syariah Indonesia, Tbk Medan Kampung Baru Branch. The population in this study was customers who pawned gold at PT Bank Syariah Indonesia, Tbk Medan Kampung Baru Branch, which was 355 people. The selection of samples in this study was based on calculations put forward by Slovin so that the sample obtained amounted to 78 respondents. Data processing is carried out with the SPSS Statistics 21 program tool. The data analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The results of this study show that the estimated value has a positive and significant effect on customer decisions, ujrah has a positive and insignificant effect on customer decisions while the estimated value and ujrah simultaneously have a positive and significant effect on customer decisions. .